Valence isomers of Aromatic Compounds: On the Mechanism of the Katz Reaction - Ulrich Burger; Pierre Jean Thorel; Yves Mentha (CHIMIA)
Lithium salts of small and medium-sized aromatic anions react with methylene chloride and alkyllithium to afford bridged bicyclobutanes or related polycyclic compounds. We demonstrate that the three new carbon-carbon bonds formed in the course of these title reactions result from a tandem of carbenoid processes. Formation of exocyclic carbenoids precedes intramolecular cheletropic addition and ring enlargement. Neither H-migration nor CH-insertion is observed throughout these processes. Key intermediates have been generated by independent routes.